The "MUSIC BOX" C(2)IPO_06: interactive hybrid robotic sculpture - Daflos, K (3rd IET International Conference on Intelligent Environments (IE 07), 2007)
The "ipo", "cipo" (K. Daflos, 2006) & "cibo" are active agents that agitate & bring the passive spectator into an active & interactive relationship with the subject. The interminglement of both, spectator (body) & subject (technology) transforms the given space into an experimental hybrid space where body & technology meet. The new medium of artworks is action-based. It involves the physical viewer participation & life's energy of human presence of the spectators or the performers. The body actions support the improvisation of self-discovery through this medium, and in turn the artwork itself becomes an improvisation. The successive transcriptions -transpositions of human presence & action in schemes, traces, signs, represent the distributed body, which is transcribed through various multiple mediums. Machine-organism inspired from: a) Gordon Pask's theory of discourse between man, machines and learning machines (P. Pangaro, 2002). b) Norbert Wiener's theory of control and communication of machines (N. Weiner, 1948).